A countermeasure development pipeline. Issue 1 (August 2016) - MacRae, Calum A.; Boss, Gerry; Brenner, Matthew; Gerszten, Robert E.; Mahon, Sari; Peterson, Randall T.
Abstract : We have developed an integrated pipeline for countermeasure discovery that, under the auspices of the National Institutes of Health Countermeasures Against Chemical Threats network, is one of the few efforts within academia that by design spans the spectrum from discovery to phase I. The successful implementation of this approach for cyanide would enable efficient proof‐of‐concept studies that would lay the foundation for a generalizable strategy for parallel mechanistic studies and accelerated countermeasure development in the face of new and emerging chemical threats.